1986
DOI: 10.1002/jcp.1041290105
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of WI‐38 cell proliferation by elevated levels of CaCl2

Abstract: Elevating the level of extracellular calcium (CaEx2+) increases the saturation density achieved by the normal human diploid cell line, WI-38, but does not change the growth rate. Day 7 cell yields remain unchanged when [CaEx2+] is between 0.5 mM and 3.0 mM, decrease when [CaEx2+] less than 0.5 mM, and increase when [CaEx2+] greater than 3.0 mM. Combining hydrocortisone with additional CaCl2 results in an additive effect on the saturation density relative to that obtained with each treatment separately. The sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Past studies have shown that proliferative responses of human keratinocytes and fibroblasts decrease as a function of age (1 -12 (13)(14)(15)(16). Changes in fibroblast and keratinocyte proliferative capacity in monolayer culture are correlated with age-related alterations in the appearance of the skin (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that proliferative responses of human keratinocytes and fibroblasts decrease as a function of age (1 -12 (13)(14)(15)(16). Changes in fibroblast and keratinocyte proliferative capacity in monolayer culture are correlated with age-related alterations in the appearance of the skin (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…It seems reasonable to suggest that RA functions in some manner to overcome the limitation imposed by insufficient Ca 2+ on fibroblast function. While it is difficult to extrapolate from monolayer and organ culture data to what might occur in intact skin, one could postulate that a progressive decrease in responsiveness to extracellular Ca 2+ in dermal fibroblasts as a function of aging (noted in previous studies by others [4,5,[24][25][26]) provides a target of opportunity for retinoid action.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of human diploid fibroblast-like cells (HDF) in culture can be modulated by a variety of culture conditions including the variation of the extracellular Ca2+ concentration. Elevated levels of extracellular Ca2+ increase the saturation density of HDF and enhance the proliferative response of quiescent monolayers to serum stimulation (Praeger and Cristofalo, 1986). Conversely, a reduction in extracellular Ca2+ arrests HDF in a quiescent Gl/GO cell-cycle state (Boynton et al, 1977;Tupper et al, 1980Tupper et al, , 1982.…”
mentioning
confidence: 99%